Analysis of resource potential for cattle developing in Serdang Bedagai regency - M Iqbal; E Mirwandhono; T H Wahyuni; N Ginting; I Sembiring (Jurnal Peternakan Integratif, 2019)
High animal production especially meat is still need to fulfilled as demand is high.This research was conducted to analyze the availability of resources in Serdang BedagaiRegency in the context of cattle developing. The study was conducted from September 2017to January 2018. This study used a survey method, the first stage of stratification (stratifiedsampling) to the sub-districts in Serdang Bedagai Regency, the second stage took purposivesampling in three sub-districts namely Dolok Masihul District, Dolok Merawan and SeiRampah, the third stage was purposively sampling of 10 farmers from each of the subdistricts. The results of this study that livestock resources in Serdang Regency Bedagai stillhave great potential in developing beef cattle business seen from natural resources, humanresources, capital and technology.